(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article analyzes the use of foreign experience in developing the small business and private entrepreneurship, and their advantages in the Republic of Uzbekistan. There cited statistics on small businesses and private entrepreneurship in different countries of the world, and its role is shown in improving the competitiveness of national economy. And also, considered the state and development of small business and private entrepreneurship in Uzbekistan.